Preferences of streaming platforms users among the youth audience - D. V. Medvedev; V. A. Nikitin (Вестник университета, 2023)
The purposes of this article are the following: to identify online cinemas that are most common among the audience studying or working at the RUDN University and to compare the results of the conducted work with the results of identical materials. The main tasks are to be named: studying the main proposals among streaming services and online cinemas in Russia; studying the findings of researches on the same topic; compiling a survey to collect primary research information; conducting surveys; summarising the achievements and formulating conclusions. During the study, students of different years aged 18 to 24 were interviewed. They formed a particular list and sequence of popular online cinemas, somewhat different from the research of the GfK agency. According to the survey results, the most attractive streaming services are Kinopoisk HD, Netflix and Ivi (formerly – ivi). In this case, their clear sequence reflects the popularity of use of platforms among students.